Complexity index in sarcoma and genomic grade index gene signatures in rhabdomyosarcoma of pediatric and adult ages. Issue 7 (10th March 2021) - Ferrari, Andrea; Iannó, Maria Federica; Carenzo, Andrea; Fortunato, Orazio; Casanova, Michela; Chiaravalli, Stefano; Bergamaschi, Luca; Bertulli, Rossella; Cattaneo, Francesca; Collini, Paola; Trama, Annalisa; Sozzi, Gabriella; et al.
Abstract: Background: Rhabdomyosarcoma (RMS), the most frequent soft‐tissue sarcoma in childhood, shows extensive heterogeneity in histology, site and age of onset, clinical course, and prognosis. Adolescents and young adults (AYA) with RMS form a subgroup of patients whose survival lacks behind that of children while diagnosed with histologically similar tumors. Procedures: A 67‐gene prognostic signature related to chromosome integrity, mitotic control, and genome complexity in sarcomas (CINSARC) is considered a powerful tool for identifying tumors with a highly metastatic potential. With this study, we investigated the prognostic value of CINSARC signature on a cohort of 48 pediatric (PEDs) and AYAs‐RMS. Results: CINSARC resulted not significantly correlated with age, suggesting other determinants to be responsible for that difference in survival. It remained a significant prognostic variable in both the groups of PEDs and AYAs. Also, genomic grade index signature was tested on the same cohort and showed very similar results with CINSARC. Conclusions: Our study showed that CINSARC correlated with outcome in RMS patients and may be potentially considered a tool to predict outcome, and so stratify RMS patients.